Korupsi dalam Perspektif Konseling Islam: Hakikat dan Penanganannya - Warlan Sukandar (Hikmah, 2018)
Corruption is an act that brings a lot of destruction, both to themselves and the nation's society. Corruption is immoral and sometimes has become a culture in a particular society . In some countries, including Indonesia and Malaysia have done a variety of ways in an effort to eradicate corruption. But it seems the corruption has become a culture in the midst of society, so that corruption does not only occur at the top of society but also more common in ordinary society. This article attempts to examine the behavior of the corruption from perspective scientific of Islamic Psychology, the essence and the ways to tackle corruption from perspective scientific of Psychology and Islam. Handling corruption is divided into three aspects, namely; preventive aspects, action aspects, and educational aspects. The assessment methodology used is content analysis to analyze the data obtained from various sources related to the study being conducted. The results of this study found that the handling of corruption from the aspect of prevention can be done by implanting twenty of Islamic personality traits to individuals. From the action aspect can be done in various ways; material sanctions, imprisonment, dismissal office, whips, suspension of certain rights to the death penalty . While from the educational aspects the handling of corruption can be done by way of providing education to all levels of society about the essence of corruption, embed anti-corruption and apply anti-corruption behavior.Keyword : Corruption , Islamic Psychology , Essence and Handling